Effect of Plant Based Diet Versus Intermittent Fasting Diet on Lipid Profile in Obese Premenopausal Women - Sadek, Yehia Mahmoud Mohamed; Emara, Hala Mohamed Hanafy; Awad, Mohamed Ahmed Mohamed; Samier, Sameh Hussien; Abdelhaliem, Heba S (Journal of Neonatal Surgery, 2025)
Introduction: The aging process correlates with a heightened risk of obesity and non-communicable diseases, including cardiovascular disease, type 2 diabetes, as well as hypertension. Nonetheless, it seems that the heightened risk of non-communicable diseases is associated with central obesity and higher waist circumference (WC), rather than general obesity or elevated BMI. Aim of the study: The purpose of this study was to determine the difference between the effects of plant based diet and intermittent fasting diet on lipid profile in obese premenopausal women. Subjects: Sixty obese premenopausal women with hyperlipidemia, were took part in this study. They were chosen from the outpatient clinic of MTI University. Their ages varied from 40 to 45 years, and their body mass index (BMI) ranged from 30 to 35 kg/m². Every participant had no history of diabetes mellitus, hypertension, malignancy, pacemaker, or hyperthyroidism. Design: Randomized controlled study, all women were randomly allocated into two equal groups; Study group (A): included 30 obese pre-menopausal women who were treated by aerobic exercises on treadmill for 30 minutes 3 sessions/ weak and plant based diet for 3 months. Study group (B): included 30 obese pre-menopausal women who were treated by aerobic exercises on treadmill for 30 minutes 3 sessions/ weak and intermittent fasting diet for 3 months. Assessment: Assessment of BMI, WHR, total cholesterol (TC), triglyceride (TG), low density lipoprotein (LDL) as well as high density lipoprotein (HDL), measurements were taken for both groups (A and B) prior to and following treatment. Results: Both plant based diet and intermittent fasting diet have significant effect in decreasing BMI, WHR, TC, LDL & TG and increasing HDL post treatment. When compared plant based diet with intermittent fasting diet post treatment, plant based diet has more significant effect. Conclusion: Plant-based diet is more effective than intermittent fasting diet through decreasing BMI, WHR, total cholesterol, LDL & total triglycrides levels along with increasing HDL level in obese premenopausal women.